Knowledge and Attitude towards Antibiotic Use among College Students in Jatinangor - Fimanggara, Brama; Istriati, Istriati; Diposarosa, Rizki (Althea Medical Journal, 2016)
Background: Lack of knowledge about antibiotics cause people to have a misconception about the useÂ of antibiotics. This may potentially lead to inappropriate use of antibiotics in the community, which is themajor reason for the spread of antibiotic resistance. This study aimed to assess knowledge and attitudesÂ toward antibiotic usage among non-medical students in Jatinangor.Methods: This study used a cross-sectional, questionnaire based survey conducted among non-medicalÂ college students in Jatinangor, sub-district of Sumedang regency, from September to October 2013. SamplesÂ were selected using convenience sampling method, with a total number of 250 samples.Results: More than half of the respondents (56.4%) had a poor knowledge regarding antibiotic use.Â Respondents who knew that antibiotics was indicated to treat bacterial infections reached 75.2%, althoughÂ 58.4% of respondents still believed that antibiotics could be used in viral infection. In terms of antibioticresistance, 72% of respondents were aware that overused of antibiotics could cause antibiotic resistance.Â In addition, respondents were generally found to have more positive attitudes toward antibiotics withÂ results over 50%, whereas more than one-third of the respondents wrongly self-medicated themselves withantibiotics.Conclusions: This study reveals that most of the respondents have poor knowledge regardingÂ antibiotics. Almost half of the respondents have a negative attitude regarding the use of antibiotics.Â Educational interventions are needed to promote prudent use of antibiotics among the college students.[AMJ.2016;3(2):269â74]DOI:Â 10.15850/amj.v3n2.792